Encouraging the Use of E-mail and Mailing Lists Among Translation Students - Alcina-Caudet, Amparo (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2003)
AbstractHow often students use IT resources is a key factor in the acquisition of skills associated to the new technologies. Strategies aimed at increasing student autonomy need to be developed and should offer resources that encourage them to make use of computing tools outside class hours. The mailing list INFOTRAD was created with the aim of encouraging the use of e-mail and of familiarising students of Translation and Interpreting with mailing lists. In this paper, we look at the chief characteristics of this list, how it came into being and the results obtained during its first six months in operation.